2021
DOI: 10.1155/2021/8819422
|View full text |Cite
|
Sign up to set email alerts
|

Compliance Model and Structure Optimization Method Based on Genetic Algorithm for Flexure Hinge Based on X-Lattice Structure

Abstract: In order to obtain a new structure of beam flexure hinge with good performance, the flexure hinge based on the X-lattice structure is researched in this paper. The truss model in the finite element method is used to model the 6-DOF compliance of the flexure hinge based on the X-lattice structure. The influence of structural parameters on the compliance and compliance ratio of flexure hinges is analyzed based on this model, and the performance is compared with the traditional beam flexure hinge of the same size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another way to decrease the wall stiffness is by using lattice structures, as recent studies have shown [41][42][43][44]. Advantages of lattice flexures are a reduced bending stiffness, a significantly lower mass, and good off-axis stiffness [41].…”
Section: D Printing Of Flexuresmentioning
confidence: 99%
“…Another way to decrease the wall stiffness is by using lattice structures, as recent studies have shown [41][42][43][44]. Advantages of lattice flexures are a reduced bending stiffness, a significantly lower mass, and good off-axis stiffness [41].…”
Section: D Printing Of Flexuresmentioning
confidence: 99%
“…Chen et al 30 created a hinge with damping layers using a strain energy approach and the Kelvin damping model, which effectively reduced vibration. Based on the X-lattice structure, Zhang et al 31 designed a new structure for the beam flexure hinge. Awtar et al 32 simplified the cantilever beam stress-strain model to facilitate the design of reed-type flexure hinges.…”
Section: Introductionmentioning
confidence: 99%